ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN - Sumadi, Sunarso & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRACT Target of this research to analyzed influence which is between motivation, environmental of job, and style leadership of headmaster to performance of teacher SMK Sub-Province Grobogan. Population is teacher SMK Sub-Province Grobogan year 2007 countedÂ  428 people. Sample taken by random, counted 86. Technique data collecting use questionnaire through validity test and reliabilities. Analysis technique use doubled linear regression. Result of analysis show motivation variable, environmental of job and style leadership of headmaster have an effect on by significant to teacher performance. Coefficient determination test equal to 0,749; meaning motivation, environmental of style and job leadership of headmaster explain equal to 74,90 percentÂ  to teacher performance, rest influenced by other variable. Keywords: motivation, environmental of job, style leadership, performance Â